2015
DOI: 10.23939/chcht09.03.287
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Chemical Surface Deposition (CSD) of CdS and CdSe Semiconductor Thin Films

Abstract: Abstract. A mathematical model of the chemical surface deposition process of CdS and CdSe thin films, which allows determining the concentration of reagents, as well as duration and temperature for CSD needed to obtain films of the set thickness was designed. The adequacy of model was tested by Fisher's criterion. The nomogram of dependence of cadmium ions content on the initial deposition parameters was built according to the results of experimental studies and approximated by mathematical dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Concentrating systems capable of increasing the heat flow density attract special attention [7,8]. The efficiency of flat solar collectors can be increased by increasing the heat exchange area, using highly thermally conductive materials, creating turbulence and changing the direction of fluid movement [9,10], as well as applying a selective coating [11]. Studies have shown that solar collectors equipped with a phase-changing material and a radiator provide longer supply of hot water in the evening and have a lower output temperature in the morning [12].…”
Section: -9969mentioning
confidence: 99%
“…Concentrating systems capable of increasing the heat flow density attract special attention [7,8]. The efficiency of flat solar collectors can be increased by increasing the heat exchange area, using highly thermally conductive materials, creating turbulence and changing the direction of fluid movement [9,10], as well as applying a selective coating [11]. Studies have shown that solar collectors equipped with a phase-changing material and a radiator provide longer supply of hot water in the evening and have a lower output temperature in the morning [12].…”
Section: -9969mentioning
confidence: 99%
“…Vibratory treatment is usually used for performing various finishing technological operations, e.g., lapping, polishing, glazing, grinding, strengthening (hardening), etc. As an example, the vibratory finishing treatment can be implemented while manufacturing semiconductors [1]. As well, the mentioned above technological operations are widely used in pharmaceutical, chemical, agricultural, mining, machine-building industries, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of this process has been made for zinc and cadmium chalcogenides [5][6][7]. It is based on determination of metal content by anodic stripping voltammetry in a water solution, prepared by dissolving thin films [8][9]. In case of HgSe films it is convenient to use measurements of coatings mass changes, since mercury selenide is difficult to dissolve in water solutions.…”
Section: Introductionmentioning
confidence: 99%